Aims and Scope of JAMES. (11th April 2023) - Griffies, Stephen M.; Fan, Jiwen; MacBean, Natasha; Schneider, Tapio
Abstract: The mission of AGU's Journal of Advances in Modeling Earth Systems ( JAMES ) is to publish original research papers that advance the science underlying Earth system models and emerging from their use. JAMES ' scope encompasses the outer envelope of the Earth system including the atmosphere, oceans, land surface, and cryosphere. It publishes papers that expand capabilities to model, understand, and predict the Earth system and the physical, chemical, and biological processes shaping it. In this editorial, we present general principles as well as specific notions that guide the strategy of JAMES ' editors in realizing the journal's mission. This document serves as an update to Griffies et al. (2021), https://doi.org/10.1029/2021MS002567 . Key Points: This Editorial presents principles that guide Journal of Advances in Modeling Earth Systems ' editors in realizing the journal's mission